Pengaruh Mendongeng Terhadap Kemampuan Menyimak Anak Usia 5-6 Tahun di TK Bina Kreatif Kecamatan Sipoholon Tahun Ajaran 2022/2023 (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Simamora, Cristina. 2023. " The Effect of Storytelling on Listening Ability of Children Aged 5-6 Years Old in Bina Creative Kindergarten, Sipoholon District, Academic Year 2022/2023 " Thesis : PK-AUD Prodi Tarutung State Christian Institute The purpose of this study was to determine the effect of storytelling on listening skills in children aged 5-6 years at Bina Creative Kindergarten, Sipoholon District, Academic Year 2022/2023 . The method used in this research is a quantitative research method with descriptive statistics . The population is all children aged 5 – 6 years in the Bina Creative Kindergarten, Sipoholon District, Academic Year 2022/2023 totaling 17 people. Data is collected by items closed questionnaire with 20 items. The results of the data analysis show that there is an effect of storytelling on listening skills in children aged 5-6 years at Bina Kreatif Kindergarten, Sipoholon District, Academic Year 2022/2023 : 1) Test requirements analysis: a) positive relationship test obtained r xy = 0, 696 > r table ( a =17 0.05, n = ) = 0.482 , thus it is known that there is a positive relationship between variable X and variable Y. b) A significant relationship test obtained t value = 3.750 > t table ( a =0.05,dk=n-2= 15 ) = 2, 131 thus there is a significant relationship between variable X and variable Y. 2). a) Influence test: Regression equation test, obtained regression equation . b) Test the hypothesis by using the F test to obtain F table = ( a = 0.05, dk quantifier k = 5 , dk denominator = n-2 = 17 -2 = 15 ) = 2.90 then F count > F table i.e. 14.04 > 2.90 . Thus Ha is accepted and H 0 is rejected.